2013
DOI: 10.1177/0098628312475037
|View full text |Cite
|
Sign up to set email alerts
|

Gaming in the Classroom

Abstract: This study tested the effectiveness of video game use for instruction of factorial designs in a research methods course. Students designed and conducted a mini study, playing Dance, Dance, Revolution, using video game scores as the dependent variable. A mixed-design analysis of variance revealed a significantly greater increase from pretest to posttest in content knowledge in the Wii activity condition compared to lecture-only and no-content control conditions. Implementing this nontraditional teaching method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Collectively, students' resistance makes teaching research courses a challenge. To counteract this, there are various types of teaching resources, such as books (e.g., Saville, 2008), research articles (e.g., Stansbury & Munro, 2013), and websites (e.g., www.TeachPsych-Science.org) dedicated to helping faculty teach research methods. However, we know little about the specific challenges faculty face, which may affect their effectiveness in teaching this important course.…”
mentioning
confidence: 99%
“…Collectively, students' resistance makes teaching research courses a challenge. To counteract this, there are various types of teaching resources, such as books (e.g., Saville, 2008), research articles (e.g., Stansbury & Munro, 2013), and websites (e.g., www.TeachPsych-Science.org) dedicated to helping faculty teach research methods. However, we know little about the specific challenges faculty face, which may affect their effectiveness in teaching this important course.…”
mentioning
confidence: 99%
“…According to Hamlen (2013), “despite assumptions that children play video games to avoid mental stimulation, children are actually motivated by the challenge and thinking required by video games.” Squire (2005) reported that Marvin voluntarily, and without provocation, spent time learning more about history from the “civelopedia” which provides players with historically accurate information about their chosen civilizations and other aspects of the game. Improved student engagement using video games was also demonstrated by Stansbury and Munro (2013; Stansbury et al, 2014) who supplemented an undergraduate-level behavioral statistics lecture by having students play the game Dance Dance Revolution (DDR) to generate scores that would be used as dependent variables while teaching the students about factorial research designs. They found, based on a pre-test/post-test comparison, that students who played DDR as part of their lecture showed a greater increase in content knowledge compared to students who received a traditional lecture on the same topic.…”
mentioning
confidence: 89%
“…The My Virtual Child© programme includes features of good teaching practices as previously proposed by various research studies, such as experiential learning opportunities (Stoloff et al, 2012), interactive activities (Wilson, 2013), social networking and interactive sites (Blessing et al, 2012;Stansbury & Munro, 2013;Twenge, 2013).…”
Section: Concluding Remarks: Implications For Practicementioning
confidence: 99%
“…Furthermore, Stansbury and Munro (2013) found that implementing nontraditional teaching methods (such as a video game to teach research methods), increased students' knowledge, interest and motivation. Wilson (2013) added the positive impact of interactive activities on students' attitudes, and Blessing, Blessing and Fleck (2012) suggested the use of social networking sites (such as Twitter).…”
mentioning
confidence: 99%